ANALISIS TENTANG FAKTOR-FAKTOR PENYEBAB PERGESERAN ADAT PERKAWINAN MASYARAKAT JAWA DESA PERKEBUNAN TELUK PANJI KECAMATAN KAMPUNG RAKYAT KABUPATEN LABUHANBATU SELATAN SUMATERA UTARA - Kuntari, Jati; Eddison, Ahmad; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The implementation of Java traditional wedding in the Bay Plantation Village Panji People Kampung District of South Labuhanbatu of North Sumatra has undergone a change. This study aims to determine what factors are the cause of the shift in the Java community customary marriage Plantation Village People Kampung Teluk Panji District of South Labuhan Batu regency of North Sumatra. Respondents in this study were 182 heads of household and 2 elders. Data collection techniques are observation, interviews, questionnaires, and documentation. The method used is the method of combination of quantitative and qualitative (mixed methodes). This method is done with the data processing result data is presented through the calculation of the percentage and given an explanation. The results showed that the factors that cause a shift in the Java community customary marriage Plantation Village People Kampung Teluk Panji District of South Labuhanbatu regency of North Sumatra is due to the cultural influence of other communities, contact with other cultures, advanced formal education system, respect for the work of someone and the desire to move forward, open system of society (open stratification), heterogeneous population, economic factors, time factors, technological factors, and confounding factors tribal/ crossbreeding.Key Words: Factor, Shift, Customary Marriages JavaÂ